2021
DOI: 10.1093/ajcn/nqaa449
|View full text |Cite
|
Sign up to set email alerts
|

Does supplementation with leucine-enriched protein alone and in combination with fish-oil-derived n–3 PUFA affect muscle mass, strength, physical performance, and muscle protein synthesis in well-nourished older adults? A randomized, double-blind, placebo-controlled trial

Abstract: Background Leucine-enriched protein (LEU-PRO) and long-chain (LC) n–3 (ω–3) PUFAs have each been proposed to improve muscle mass and function in older adults, whereas their combination may be more effective than either alone. Objective The impact of LEU-PRO supplementation alone and combined with LC n–3 PUFAs on appendicular lean mass, strength, physical performance and myofibrillar protein synthesis (MyoPS) was investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 68 publications
0
60
0
1
Order By: Relevance
“…Another possibility is that the participants in the studies reporting no advantageous effects of LC n -3 PUFA supplementation were consuming sufficient protein, precluding the ability to observe an ergogenic effect of LC n -3 PUFA intake. Although most of the LC n -3 PUFA supplementation studies do not report protein intake [ 28 , 47 , 51 ], protein intakes were higher (~ 1.3 g/kg/day) among participants in the study by Murphy et al [ 50 ], which reported no favorable effects of LC n -3 PUFA, compared to ~ 0.9 g/kg/day in the study by Rodacki et al [ 27 ]. Future work that examines how LC n -3 PUFA intake and resistance exercise training influence skeletal muscle mass, strength, and physical performance in older women and men may resolve these discrepancies and provide important information for the field.…”
Section: Lc N -3 Pufas and Skeletal Muscle Adaptation To Resistance Exercise Trainingmentioning
confidence: 94%
See 3 more Smart Citations
“…Another possibility is that the participants in the studies reporting no advantageous effects of LC n -3 PUFA supplementation were consuming sufficient protein, precluding the ability to observe an ergogenic effect of LC n -3 PUFA intake. Although most of the LC n -3 PUFA supplementation studies do not report protein intake [ 28 , 47 , 51 ], protein intakes were higher (~ 1.3 g/kg/day) among participants in the study by Murphy et al [ 50 ], which reported no favorable effects of LC n -3 PUFA, compared to ~ 0.9 g/kg/day in the study by Rodacki et al [ 27 ]. Future work that examines how LC n -3 PUFA intake and resistance exercise training influence skeletal muscle mass, strength, and physical performance in older women and men may resolve these discrepancies and provide important information for the field.…”
Section: Lc N -3 Pufas and Skeletal Muscle Adaptation To Resistance Exercise Trainingmentioning
confidence: 94%
“…One working hypothesis is that supplementation with LC n -3 PUFAs increases the EPA and DHA content of skeletal muscle potentiating rates of mixed MPS in response to amino acid provision [ 48 , 49 ] leading to increases in skeletal muscle mass and strength [ 27 , 28 , 47 ]. However, both Da Boit et al [ 28 ] and Murphy et al [ 50 ] observed no effect of LC n -3 PUFA supplementation on integrated myofibrillar MPS rates measured over 3–4 days. McGlory et al [ 52 ] also failed to detect an influence of 8 weeks of 3.5 g/day EPA and 0.9 g/day DHA on acute (3 h) rates of myofibrillar MPS in response to oral protein feeding with or without resistance exercise in young men [ 48 , 49 ].…”
Section: Lc N -3 Pufas and Skeletal Muscle Adaptation To Resistance Exercise Trainingmentioning
confidence: 97%
See 2 more Smart Citations
“…It is understood that low-protein intake may be a risk factor for sarcopenia since a greater amount of protein are required to stimulate MPS in the elderly ( 8 , 12 ). However, many human dietary intervention studies have shown little or no impact of protein ( 22 , 23 ), leucine ( 24 26 ), or IAA ( 27 ) supplementation on muscle mass and/or strength in non-exercising older adults. Therefore, resistance exercise, regulation of other nutrient sensors that modulate MPS aside from AA, and/or even greater amounts of protein supplementation/intake than those offered in this study may be essential tools to fight sarcopenia in healthy older adults.…”
Section: Introductionmentioning
confidence: 99%